Comparison of Antioxidant Activity of Ethanolic, Methanolic, n-Hexan, and Aqueous Extract of Parkia speciosa Peel based on Half -Maximal Inhibitory Concentration Through Free Radical Inhibition - Nurdyansyah, Fafa; Widyastuti, Dyah Ayu (Universitas PGRI Semarang, 2020)
The objectives of this study was to determine the half maximum inhibitory concentration (IC50) from four types of Parkia speciosa peel extracts (ethanol, methanol, n-hexane, and aqueous) through DPPH free radical inhibition. First Parkia’s peel extract made by drying the Parkia’s peel that has been sorted, then crushed and mashed with a blender. Parkia’s powder then macerated for 3 replication using each type of solvent and then solvent evaporation was carried out using a rotary vacuum evaporator. The evaporated extract produced then tested for antioxidant activity using the IC50 method and phytochemical screening was performed to analyze the potential content of functional compounds. The results showed that all types of solvents dissolve alkaloid compounds (except water extract), flavonoids, saponins, tannins, and phenols. IC50 values produced from the four types of petai bark extract using methanol, ethanol, water, and n-hexane solvents sequentially were 76.92; 111; 136; and 201 ppm. Methanol extract had the lowest IC50 value of 76.92 ppm which resulted that the methanol extract of petai skin had a strong (active) antioxidant strength compared to others.Keywords: Antioxidant, Exctract, Parkia’s peel, IC50